Perencanaan Perawatan Mesin Pengupas Sabut Kelapa - Yogi Putra; harfardi harfardi; M Elfian Hadi (Jurnal Teknik Mesin, 2017)
Coconut is a versatile plant and almost all parts of coconut can be utilized by humans. In the processing of coconut fruit, namely stripping, decomposition and sieving, but in the stripping process there are still many uses manually. Therefore, coconut husk peeler is made. This machine can facilitate the stripping of coconut fiber to separate it from the coconut shell. The working principle of this machine is to use knives that are located in the shaft and connected to the motor as a driver by using electric power. The way to do it is that the coconut that has been taken from the tree that is ready to be peeled is placed on the shaft, pressed using a lever to the shaft that has a knife, then the shaft will rotate and the knife will pull the coconut fiber. For the smooth use of coconut coir peeler, proper and efficient maintenance planning is needed so that the engine can run continuously, where the engine components that are treated are shaft, motor, gear, pully and belt. In planned care includes daily, weekly and monthly care. So care must be done well and optimally in order to get good treatment results